95 EXPLORING HIP FRACTURE OUTCOMES IN POST-ACUTE REHABILITATION: A MULTI-SITE AUDIT. (25th October 2022) - McDaid, E; Long, S; Curtin, C; Burke, C; O'Brien, K; Cogan, L; Ahern, E; Mello, S; O'Connor, M
Abstract: Background: In 2020, 28% of all hip fractures in Ireland were discharged to off-site rehabilitation. The annual Irish Hip Fracture Database (IHFD) report captures patient outcomes at the point of acute discharge however patient outcomes at discharge from offsite rehabilitation are unknown. Methods: A multi-site retrospective audit was completed examining hip fracture outcomes for patients admitted to four post-acute rehabilitation hospitals during 2021, using IHFD HIPE portals as well as local databases. Descriptive statistics including demographics, pre-fracture mobility as well as outcomes measured including acute length of stay, rehabilitation length of stay, discharge destination and independence with mobility on discharge from rehabilitation. A comparison analysis between sites was completed. Results: A total of 445 patients were admitted post hip fracture to the four rehabilitation hospitals in 2021. Most were female (69%, n=307), mean age 82.5, 49% lived alone and most (55%) had low pre-fracture mobility as measured by New Mobility Score of 0-6. The mean acute length of stay was 11.8 days and rehabilitation stay 37.6 days. Most (90.2% of complete data, n=333) discharged home, 4.5% (n=17) were transferred to hospital, 3.2% (n=12) were newly admitted to nursing home and 1% (n=4) died. Most (82.2% of complete data, n=256) were independently mobile (CAS 6) at discharge from rehabilitation. There was no significant difference in patient profile between sites however there were significant difference in both acute length of stay (median range 8-13days) as well as rehabilitation length of stay (median range 16-39days). Conclusion: The findings of this audit provide a new perspective on recovery post hip fracture and insight into longer term hip fracture outcomes. It shows that data collection is feasible in off-site rehabilitation units and should be considered for inclusion in the IHFD. Further work could explore the establishment of standards of care in the post-acute phase of hip fracture rehabilitation.